Highly durable Sr-doped LaMnO3-based cathode modified with Pr6O11 nano-catalyst for protonic ceramic fuel cells based on Y-doped BaZrO3 electrolyte. Issue 10 (August 2022) - Sun, Keqiang; Yu, Zhexiang; Ni, Qing; Li, Yu; Xu, Dong; Gu, Yiheng; Zheng, Yifeng; Chen, Han; Ge, Lin; Guo, Lucun
Abstract: Sr-doped LaMnO3 (LSM) is one of the state-of-the-art cathodes with outstanding chemical stability but suffers from poor electrochemical activity. It is promising that LSM can be used as good cathode for protonic ceramic fuel cells (PCFCs), provided that its catalytic activity can be improved. Herein, we have developed a high-performance and durable LSM-based cathode used for PCFCs with stable Y-doped BaZrO3 electrolyte. In this work, commercial LSM cathode is mixed with high-performance BaZr0.85 Y0.15 O3-δ particles. Pr6 O11 nano-catalysts are homogeneously dispersed into the composite cathode, resulting in a significant decrease in the cathode polarization resistance from 0.51 to 0.12 Ω·cm 2 at 600 °C. The power output improves by ~96% at 600 °C. Distribution of relaxation time analysis indicates that the processes of oxygen adsorption/dissociation and oxygen species diffuse to triple phase boundary sites are significantly promoted by Pr6 O11 . Furthermore, the 100 h stability tests show that the modified cathode is extremely stable. Highlights: The first-generation LSM cathode was optimized and used for BZY-based PCFCs. The optimized cathode showed the lowest ever R p of traditional MIEC cathodes. The optimized cathode exhibited outstanding durability.